Maxillary Sinus Augmentation with Xenogenic Collagen-Retained Heterologous Cortico-Cancellous Bone: A 3-Year Follow-Up Randomized Controlled Trial - Francisco Correia; Sónia Gouveia; António Campos Felino; Ricardo Faria-Almeida; Daniel H. Pozza (MDPI AG, 2024)
Sinus augmentation procedures have become a valuable solution for patients with posterior maxillary edentulism. The objective of this study was to explore the efficacy and safety of porcine xenograft with collagen supplementation as a potential alternative to autologous bone grafts in lateral sinus augmentation over a three-year follow-up period. Twelve patients, each with bilateral posterior maxillary edentulism, were enrolled and randomly allocated to receive either a porcine xenograft or an autologous graft. Comprehensive assessments, including clinical and radiographic evaluations, were conducted at specific intervals, including implant stability, marginal bone loss, prosthetic and biological complications, and patient preferences. The results demonstrated no significant differences between the two graft materials in terms of implant survival, marginal bone loss, and patient preferences after three years of follow-up. Only one implant was affected by peri-implantitis, and prosthesis-related complications were present in one patient possibly due to bruxism. In conclusion, these findings suggest that a porcine xenograft with collagen supplementation may be a viable alternative to an autograft in lateral sinus augmentation procedures. The high implant survival rate, minimal complications, and patient satisfaction indicate the potential clinical relevance of this graft material and should be further investigated to confirm these promising results.